2017
DOI: 10.1177/1059840517737140
|View full text |Cite
|
Sign up to set email alerts
|

Social and Psychological Factors Related to Risk of Eating Disorders Among High School Girls

Abstract: Prevalence of eating disorders (EDs) has increased among adolescents in Arabic and Western countries. The purposes are to identify the risk of ED and psychosocial correlates of risk of ED among high school girls in Jordan. The researchers employed a cross-sectional, correlational design using 799 high school girls from governmental and private schools in the central region of Jordan. The results indicate that prevalence of the risk of ED was 12%. The risk of ED had significant and positive correlation with bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 20 publications
0
28
1
2
Order By: Relevance
“…This same finding was observed in another Brazilian study: 8 attending a private school appeared to be a condition that increases the risk of abnormal eating behaviors (p-value<0.001). However, this finding differs from Jordanian researchers, 23 who observed no association between the type of school and risk behaviors for eating disorders (p-value>0.05). A Brazilian study developed by Hermont et al 15 did not verify this association neither, but it found proportionally more cases of risk behavior among students from private schools compared to those from public schools.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This same finding was observed in another Brazilian study: 8 attending a private school appeared to be a condition that increases the risk of abnormal eating behaviors (p-value<0.001). However, this finding differs from Jordanian researchers, 23 who observed no association between the type of school and risk behaviors for eating disorders (p-value>0.05). A Brazilian study developed by Hermont et al 15 did not verify this association neither, but it found proportionally more cases of risk behavior among students from private schools compared to those from public schools.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidence points to an increasingly wide distribution of eating disorders worldwide 22 . Being female and adolescent do trigger eating disturbances and risk of eating disorders 23 . Our results show that almost half of the studied adolescents was at risk for bulimia, which is considered high.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Prevalence of anorexia nervosa and bulimia nervosa have increased among adolescents in Arabic, Western [7] and now a clinical problem in Asian countries like Pakistan, India and Bangladesh etc. Nearly 50% of adolescents had the chance to become overweight during the transition to adulthood [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 50% of adolescents had the chance to become overweight during the transition to adulthood [8]. Anorexia nervosa is an increasingly common eating disorder in adolescent girls, in Western societies [9], and is the third most common chronic disease in adolescent girls, that's why the risk of disordered eating attitudes is highly prevalent among adolescent girls [7].…”
Section: Introductionmentioning
confidence: 99%